Indicator development of internal quality assurance of the school providing both general and vocational education systems: a case study of Kampong Chheuteal High School, Kingdom of Cambodia - Bunhe Harth (Chulalongkorn University, 2013)
Thesis (M.Ed.)--Chulalongkorn University, 2012